The 'aiteo' / 'aiteomai' Distinction in the New Testament: A Proposal - Danove, Paul L. (Filología neotestamentaria, 2012)
This article investigates the seventy New Testament occurrences of aiteo to determine the motivation for and distinctive implications of the verb’s active and middle forms. The introductory discussion specifies the semantic and syntactic characteristics of aiteo and develops two features that have implications for distinguishing verbal usages. The discussion then proposes the distinction between active and middle forms and demonstrates this distinction in occurrences of the verb.